5(x+7)=-30(x+2)

Simple and best practice solution for 5(x+7)=-30(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+7)=-30(x+2) equation:


Simplifying
5(x + 7) = -30(x + 2)

Reorder the terms:
5(7 + x) = -30(x + 2)
(7 * 5 + x * 5) = -30(x + 2)
(35 + 5x) = -30(x + 2)

Reorder the terms:
35 + 5x = -30(2 + x)
35 + 5x = (2 * -30 + x * -30)
35 + 5x = (-60 + -30x)

Solving
35 + 5x = -60 + -30x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '30x' to each side of the equation.
35 + 5x + 30x = -60 + -30x + 30x

Combine like terms: 5x + 30x = 35x
35 + 35x = -60 + -30x + 30x

Combine like terms: -30x + 30x = 0
35 + 35x = -60 + 0
35 + 35x = -60

Add '-35' to each side of the equation.
35 + -35 + 35x = -60 + -35

Combine like terms: 35 + -35 = 0
0 + 35x = -60 + -35
35x = -60 + -35

Combine like terms: -60 + -35 = -95
35x = -95

Divide each side by '35'.
x = -2.714285714

Simplifying
x = -2.714285714

See similar equations:

| -5(x+4)+3x+5=5x+12 | | -7(x+3)+3x+7=5x+11 | | ((d-4)/(4))^(2)=64 | | 1/3*6h=20 | | -3(2x+5)=7x+1 | | 7(x-7)+2=9-(x+6) | | 3(x-3)=2-8x | | x-3=.75(2-x)+6 | | 2h-3h=15 | | X/0.4=11.25 | | 11x^2=44x | | 5x/x=(8x^3)/x^2 | | Y-4=-8.4 | | lnx^2+3x-1=0 | | -(-2n-5)=-13-n | | 2(3*-4)=22 | | x11/20*30 | | x=11/30x230 | | 4k-5=6k+1 | | 5(m-4)=2m+3 | | -2(z-11/5)=3z | | 2x^2-6x-9=89 | | 18=-8x+6x | | 7+6x+6x=47 | | 4x^2-16x-33=0 | | 5/6x-7/8=1/6x-1/4 | | 3/2x-(3-4x)=1/3 | | 3(3)+2(5)=60x-500 | | 5+14a=9x-5 | | 2/3×-11=14 | | -.12x^2+2.4x=8 | | y=7sinx-4 |

Equations solver categories